Pollera y vestido, le langage socioethnique du vêtement : migration, génération, profession et instruction - Véronique Marchand (Cahiers des Amériques Latines)
Most tradeswomen of La Paz, the capital of Bolivia, enter into a migratory process starting from the country and characterize themselves by a particular appearance of dress, the principal attributes of which are the pollera (ample skirt), the sombrero (bowler hat) and the manta (shawl). This dress distinguishes them both from the "Indian Women", dressed in a more sober way and from the señoras, "the ladies of the town", de vestido, that is : dressed in the western way. But some of the tradeswomen are also de vestido. How to explain this distinction? How can the women leave their group of the women de pollera called also cholas ["Indian Women in social ascent"]? The women de pollera belong to the first generation of migrants and seem more tied to the professional world of market. These variables are necessary to account this dress differentiation, but they are not sufficient because some women of the second or third generation are also de pollera. The sole really relevant criterion is the level of instruction, combined with other variables. As a matter of fact, to be de vestido hides a plan of social ascent correlated to the higher level of instruction.